Enhanced Conductivity of Multilayer Copper–Carbon Nanofilms via Plasma Immersion Deposition - Weng, Haotian; Zhang, Xiwu; Liu, Xuan; Tang, Yunhui; Yuan, Hewei; Xu, Yang; Li, Kun; Huang, Xiaolu (Nano-Micro Letters, 2025)
Although room-temperature superconductivity is still difficult to achieve, researching materials with electrical conductivity significantly higher than that of copper will be of great importance in improving energy efficiency, reducing costs, lightening equipment weight, and enhancing overall performance. Herein, this study presents a novel copper–carbon nanofilm composite with enhanced conductivity which has great applications in the electronic devices and electrical equipment. Multilayer copper–carbon nanofilms and interfaces with superior electronic structures are formed based on copper materials using plasma immersion nanocarbon layer deposition technology, effectively enhancing conductivity. Experimental results show that for a five-layer copper–carbon nanofilm composite, the conductivity improves significantly when the thickness of the carbon nanofilm increases. When the carbon nanofilm accounts for 16% of the total thickness, the overall conductivity increases up to 30.20% compared to pure copper. The mechanism of the enhanced conductivity is analyzed including roles of copper atom adsorption sites and electron migration pathways by applying effective medium theory, first-principles calculations and density of states analysis. Under an applied electric field, the high-density electrons in the copper film can migrate into the nanocarbon film, forming highly efficient electron transport channels, which significantly enhance the material’s conductivity. Finally, large-area electrode coating equipment is developed based on this study, providing the novel and robust strategy to enhance the conductivity of copper materials, which enables industrial application of copper–carbon nanocomposite films in the field of high conductivity materials. Highlights: 1 With plasma immersion deposition technology, multilayer copper–carbon nanofilms were fabricated and conductivity can achieve up to 30.20% increase compared to pure copper. 2 By applying effective medium theory, first-principles calculations, and density of states analysis, the critical roles of copper atom adsorption sites and electron migration pathways within the nanocarbon film were analyzed, elucidating the mechanism of the conductivity enhancement. 3 Large-scale electrode coating equipment suitable for industrial production was developed.